THE EFFECT OF GUIDED INDUCTION AND MENTAL DEDUCTION IN TEACHING ARABIC GRAMMAR TO NON-NATIVE SPEAKERS IN DEVELOPING THEIR WRITING SKILLS - Sana’a Hasan mahmoud suleiman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to identify the effect of guided induction and mental deduction in teaching Arabic grammar to non-native speakers in developing their writing skills, and the study relied on the quasi-experimental approach, and the study sample members consisted of (15) students from the language center at the university of Jordan, where distributed equally randomly into three groups: the first experimental group in which the guided induction pattern was applied to its members, the second experimental group in which the mental induction pattern was applied to its members, and the control group that was taught in the usual way, and the pre-post application of the writing skills test was conducted. The results showed that there are statistically significant differences between the averages of the writing skills test scores between the control group and the experimental group (guided induction) in favor of the experimental group, and the presence of statistically significant differences between the means of writing skills test scores, between the control group and experimental group (mental deduction pattern), in favor of the experimental group. In light of the results of the study, a set of recommendations were presented.